The Efectiveness of Using Interactive Learning Media in Enhancing Learning Motivation and Science Literacy of 6th Grade Elementary School Student on the Topic of World Continents - Efi Tasfiyatul Millah; Dede Trie Kurniawan; Yunus Abidin (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
Students are still not fully involved in the learning process, which causes their ability to develop literacy skills, especially scientific literacy, to be far from expectations. Students are overloaded with concepts from limited learning sources, which still restrains them from exploring their inner potentials. The use of interactive learning media has become one of the efforts to support learning in line with the nature of the students' era. This research aims for a deeper understanding of the effectiveness of using Interactive Learning Media in efforts to enhance students' learning motivation and science literacy. The researcher employs qualitative methods and a descriptive approach to describe and analyze the effectiveness of using Interactive Learning Media. Data collection techniques include interviews, observations, and documentation. This research was conducted on 6th-grade students at SDN Tenjolaya 1. The research results show that the use of interactive learning media increases student enthusiasm in the learning process by observing an increase in student engagement and participation in learning. In addition, the iterative science skills, such as the ability to observe and analyze data, show significant development. Students also provided positive feedback regarding the use of interactive learning media, which made the conducted lessons more enjoyable and easier to understand. Based on the research results, it can be concluded that the use of interactive learning media is effective in improving students' learning motivation and science literacy